PERAN SECTION LOGISTIC ACCOUNTING DEPARTEMENT DALAM MENUNJANG KELANCARAN OPERASIONAL DI LUWANSA BEACH RESORT - Dea Arme Harahap; Agus Wahyudi (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2022)
The author is motivated to write about the role of the Section Logistic Accounting Department in supporting operational smoothness at Luwansa Beach Resort because of the difficulties he frequently encounters while carrying out field work practices in the logistics section in procuring goods to support smooth operations at Luwansa Beach Resort. The role of the logistics department is very influential in the smooth running of operations, where the logistics section purchases goods for each department that requires goods receipt and checking, storage, payment, and cost reduction so that cost overruns do not occur, which can cause losses. The research method used was qualitative, involving conducting interviews, observing, and documenting informants at Luwansa Beach Resort in the accounting department and several departments that order goods in the logistics section, namely the food and beverage department, the housekeeping department, and the engineering department. Data analysis techniques by doing data reduction, data presentation, and concluding. The results of this study indicate that the role of the logistics accounting department section is very good in supporting smooth operations at Luwansa Beach Resort.